Mycotoxins in Feed Grains and Ingredients - Herrman, Tim J. (My University, 2002)
This publication discusses the cause, clinical signs, government regulations, reconditioning/ detoxification strategies, and detection technology associated with mycotoxins in grain.
MF2061-2002_05
Keywords: MF2061; Crops; Equipment and structures; livestock; MF